Exploratory study on the professional situation of hotel directors - Dias, Á.; Ferreira, R.; Garrido, F. M. (International Journal of Services, Economics and Management, 2021)
This study evaluates the professional situation of the hotel managers, through the remuneration paid and if this remuneration is only a monthly wage or there are other types of benefits. Regarding the remuneration indexed to objectives, from the people consulted in this study, the conclusion is that it’s still not a generalised practise in the hotel industry. Adding to that, we found that between women and men who are in the same profession as hotel managers, generally speaking there are more men. This study was carried out with hotel managers affiliated to the Associação de Directores de Hotéis de Portugal. The results show that the average income is about 35,000 euros per year, corresponding to a gross monthly salary of 2,961.89 euros. People working in countries outside the EU earn better salaries than people working in Portugal. It was found that, although the profession is predominantly male, there were no changes in gross income when compared to the gender level. Most respondents (51.5%) do not receive any annual performance awards.